Biotransformation as a source of potential controlling natural mixtures of Sitophilus zeamais. (October 2022) - Beato, M.; Usseglio, V.L.; Pizzolitto, R.P.; Merlo, C.; Dambolena, J.S.; Zunino, M.P.; Zygadlo, J.A.; Omarini, A.B.
Abstract: The mycelium of Pleurotus sapidus can be used as a biocatalyst for the organic biosynthesis due to the presence of enzymes such as lipoxygenases. The aim of this work was to improve the pesticide effect of α- and β-pinenes, the main components of Pinus spp. essential oils, to be used against pest through the bioconversion process. The lyophilized mycelium of P. sapidus was used as a biotransformation tool to upgrade the bioactivities of these monoterpene hydrocarbons. The biopesticide capacity of the mixtures of compounds obtained by bioconversion of pinene isomers was evaluated against Sitophilus zeamais . Additionally, the differences in the biotransformation products were determined. The mixture of α-pinene biotransformed products showed the best repellence against S. zeamais (RI100μL/L  = −63.33 ± 15.85% at 120 min); however, both biotransformed mixtures presented low toxic effects (LC50  > 500 μL/L), while the pure compounds presented medium toxicities (LC50 α-pinene = 296.65 μL/L and LC50 β-pinene = 310.47 μL/L). Thus, the biotransformation of low-cost essential oils proves an alternative process to develop environmentally-friendly repellents by recycling forest industry side-streams. Graphical abstract: Image 1 Highlights: The mycelium of P. sapidus has the ability to bioconvert pinene isomers. A differential bioconversion rates of the pinene isomers was obtained. The biotransformation products were repellent to S. zeamais but not cause mortality. This is an alternative to reuse food and forestry wastes and produce new pesticides.